2010
DOI: 10.1097/prs.0b013e3181d0ac75
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Physical Properties and Histologic Evaluation of Injectable Dermicol-P35 Porcine-Collagen Dermal Filler

Abstract: Compared with several hyaluronic acid-based dermal fillers, Dermicol-P35 exhibited lower extrusion force, higher viscosity under low shear rate, and a higher modulus of elasticity. Results of histologic evaluation indicated that Dermicol-P35 27G did not elicit an inflammatory response and was well integrated within the host tissue. Together, these results suggest that Dermicol-P35 27G offers several advantages that may result in improved clinical experiences for both patients and clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…If the size of the cannula is too small for the material to expel easily, it will require high forces to expel which may be dangerous to patients and physicians. Studies have shown that increasing the cannula size and the required force for injection has a negative effect on the physician's ability to control the syringe [33] [34]. A study was conducted on the extrusion forces of syringes expelled by rheumatoid arthritis patients with hand impairment [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the size of the cannula is too small for the material to expel easily, it will require high forces to expel which may be dangerous to patients and physicians. Studies have shown that increasing the cannula size and the required force for injection has a negative effect on the physician's ability to control the syringe [33] [34]. A study was conducted on the extrusion forces of syringes expelled by rheumatoid arthritis patients with hand impairment [35].…”
Section: Discussionmentioning
confidence: 99%
“…The values found in our study of ~1 N to 4 N are much less than those found in the cited study. In addition, the mean extrusion forces of porcine-collagen dermal fillers were measured to evaluate injectability [33]. The study found that the lowest collagen dermal filler had a mean extrusion force of 7.7 ± 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lorenc et al . () used Herovici's polychrome to evaluate the constructive remodelling of skin defects with porcine collagen dermal filler. These investigators showed that, as with the non‐crosslinked ECM scaffold in the present study, the porcine collagen promoted the de novo synthesis of new type I collagen within the implant with little or no encapsulation of the scaffold material, similar to our results with the non‐crosslinked ECM scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…80% of the contractile force of uninjured muscle, a result that would indicate that, while ECM scaffold materials promote the regeneration of skeletal muscle, they minimize but do not eliminate the formation of scar tissue (Valentin et al, 2010). Recently, Lorenc et al (2010) used Herovici's polychrome to evaluate the constructive remodelling of skin defects with porcine collagen dermal filler. These investigators showed that, as with the non-crosslinked ECM scaffold in the present study, the porcine collagen promoted the de novo synthesis of new type I collagen within the implant with little or no encapsulation of the scaffold material, similar to our results with the non-crosslinked ECM scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Fillers with porcine collagen (PC) have also been used with good cosmetic results and few adverse reactions. 38 It seems that PC does not require previous skin testing; it induces less inflammatory response than BC; histopathologic evaluation demonstrates that PC seems integrated within the host tissue, being difficult to distinguish by conventional histopathology between porcine and HC bundles (see Fig. 4B).…”
Section: Transitory Biodegradable or Resorbable Implantsmentioning
confidence: 96%